2018
DOI: 10.1097/hjh.0000000000001589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of brachial–ankle pulse-wave velocity in patients with heart failure with preserved left ventricular ejection fraction

Abstract: Identifying complications of PAD and measuring baPWV values in HFpEF patients can improve risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…An incident HF diagnosis was carried out by a specialist and was based on clinical assessment, chest X-ray, and echocardiography [26]. Incident CVD was defined as the composite of coronary revascularization, unstable angina pectoris, and nonfatal myocardial infarction [27]. During the 2-year follow-up, all subjects were administered the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and the Kansas City Cardiomyopathy Questionnaire (KCCQ), which are two widely used disease-specific quality-of-life measures for patients with HF [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An incident HF diagnosis was carried out by a specialist and was based on clinical assessment, chest X-ray, and echocardiography [26]. Incident CVD was defined as the composite of coronary revascularization, unstable angina pectoris, and nonfatal myocardial infarction [27]. During the 2-year follow-up, all subjects were administered the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and the Kansas City Cardiomyopathy Questionnaire (KCCQ), which are two widely used disease-specific quality-of-life measures for patients with HF [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data were summarized as percentages for categorical variables and as the mean ± standard deviation (SD) for continuous variables. The sample size was calculated based on previous studies [27,30] and 80% power. Comparisons between all variables from multiple groups were assessed by the χ 2 test, Kruskal-Wallis test, or one-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that a low baPWV and a high baPWV predict a worse prognosis in patients with heart failure and preserved ejection function. 24 Therefore, when using baPWV in cohorts with severe disease conditions in both clinical and research settings, diseases such as ASO and arrhythmia, should not only be excluded but a specific exclusion criteria should also be considered. 8…”
Section: Discussionmentioning
confidence: 99%
“…When the terms brachial-ankle PWV and cardiovascular events/prognosis were entered as key words in PubMED, a total of 55 studies examining the usefulness of the brachial-ankle PWV as a marker to predict future cardiovascular events or prognosis were found. Among these, 22 had been conducted in subjects without a history of CVD and 23 had been conducted in subjects with CVD (including CKD) (i.e., 11 studies on CKD, 14 studies on coronary artery disease, 3 studies on heart failure, and 6 studies on cerebrovascular disease) 69 , 70 , 84 136 ) . These studies confirmed the usefulness of brachial-ankle PWV as a predictor of the risk of cardiovascular disease.…”
Section: Is Brachial-ankle Pwv Useful For Cardiovascular Risk Stratifmentioning
confidence: 99%